Strategies for Managing Work/Life Interaction among Women and Men with Variable and Unpredictable Work Hours in Retail Sales in Québec, Canada. (August 2014) - Messing, Karen; Tissot, France; Couture, Vanessa; Bernstein, Stephanie
Increasingly, work schedules in retail sales are generated by software that takes into account variations in predicted sales. The resulting variable and unpredictable schedules require employees to be available, unpaid, over extended periods. At the request of a union, we studied schedule preferences in a retail chain in Québec using observations, interviews, and questionnaires. Shift start times had varied on average by four hours over the previous week; 83 percent had worked at least one day the previous weekend. Difficulties with work/life balance were associated with schedules and, among women, with family responsibilities. Most workers wanted: more advance notice; early shifts; regular schedules; two days off in sequence; and weekends off. Choices varied, so software could be adapted to take preferences into account. Also, employers could give better advance notice and establish systems for shift exchanges. Governments could limit store hours and schedule variability while prolonging the minimum sequential duration of leave per week.